"The Contemporary Russian Poet Comes Out and Sorta Drops Us a Hint": Toward a Pragmatics of the Artistic Utterance. (3rd July 2018) - Arsen'ev, Pavel
Abstract : This article examines the creation of a speaking subject in contemporary Russian poetry, its relationship to political action and the expectations readers have for particular stylistic habits, especially those of the avant-garde. These features stand out against the context of other poetic movements, especially Futurism/Formalism and the Oberiu.